2001
DOI: 10.1002/bip.1011
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of near‐IR excited Raman spectra of crystalline hen egg‐white lysozyme

Abstract: Near-IR excited Raman spectroscopy was applied to examine the structural change of hen egg-white lysozyme in tetragonal crystals at low temperatures. There was little difference found in the amide I and amide III regions between the spectra observed at 77 and 298 K, suggesting that the secondary structures of lysozyme were conserved in the temperature range from 77 to 298 K. Several bands arising from the protein side chains, particularly the methylene and phenylalanyl groups, showed significant changes in eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…In recent years, usage of the Raman techniques in spectroscopic characterization of the lysozyme has gained great importance and attracted large interest of the researchers 21–23. In the Raman study of crystalline hen egg‐white lysozyme,24 Amide I (1657 cm −1 ) and Amide III (1259 cm −1 ) bands can be observed, respectively. The band at 1554 cm −1 is characterized as Trp residue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, usage of the Raman techniques in spectroscopic characterization of the lysozyme has gained great importance and attracted large interest of the researchers 21–23. In the Raman study of crystalline hen egg‐white lysozyme,24 Amide I (1657 cm −1 ) and Amide III (1259 cm −1 ) bands can be observed, respectively. The band at 1554 cm −1 is characterized as Trp residue.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] In the Raman study of crystalline hen egg-white lysozyme, 24 Amide I (1657 When the Raman spectrum of lysozyme adsorbed mPHEMA is evaluated amide-I band appears at 1657 cm 21 (Fig. 6).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…It is observed that: (1) the intensity of this band drastically decreases for temperature going from −65 to −40 • C (increase in hydrophobicity); (2) the intensity remains almost constant in the temperature range of -40 and 90 • C. The band intensity of 1005, 1013, and 1033 cm −1 , attributed to different residues, does not show remarkable changes which signifies no remarkable conformational changes in Phe, and Trp residues for this protein with temperature. Guo et al (2006) performed various measurements on lysozyme with different concentration (10 and 400 mg/ml) using various techniques and revealed that lysozyme with lower concentration shows the protein stability at 80 • C whereas lysozyme with higher concentration shows a conformational change in protein secondary structure profile even at 70 • C. Similar trend is also found by Nara et al (2001) up to RT and is attributed to the modification in Phe or their surroundings. Fig.…”
Section: Lysozymementioning
confidence: 57%
“…2(b), in which both the bands (1005 and 1033 cm −1 ) undergo the steadily decrease in temperature. This shows that when the temperature is decreased it causes the access of water to surface residues of protein (Nara et al, 2001) as expected by water-protein interaction as a function of temperature. The original information which 2D-correlation spectra carry about is that also the 830 and 855 cm −1 vibrational bands decrease with temperature.…”
Section: Bovin Serum Albumin (Bsa)mentioning
confidence: 60%
See 1 more Smart Citation